Relasi Pesantren, Alam, dan Spiritualitas Islam di Kabupaten Wonosobo: Telaah Posthumanisme dan Ekoteologi - Moch. Muhaemin; M. Mujib; Mudzakkir Mudzakkir; Iman Fadhilah; Moch. Lukluil Maknun (Balai Penelitian dan Pengembangan Agama Semarang, 2025)
Pesantren, as a central institution of Islamic education in Indonesia. These institutions face contemporary challenges, particularly the demand to redefine the relationship between humans and nature and to reinterpret the role of humans as khalifah on earth. The era of posthumanism invites the present generation to critique anthropocentrism, and ecotheology offers a theological perspective on the sustainability of non-human life. This study seeks to portray the discourses and practices in responding to these two perspectives through case studies in several pesantren in Wonosobo. The findings show that, indirectly, whether consciously realized or not, pesantren have practiced and articulated the role of human–nature relations. An understanding of balance between the two has been embedded in teachings, learning processes, and practices. However, these good practices have not yet been implemented optimally. Various obstacles and challenges remain, including the lack of synergy in the learning curriculum, the economic capacity of pesantren, and the formation of parents’ perceptions that remain focused on the core objective of pesantren, which targets students to become experts solely in religious fields, while neglecting or being less receptive to other forms of development. Nevertheless, pesantren communities are not unprepared to face contemporary challenges, as they are shaped and facilitated by skills and direct practices in addition to learning from books and classical texts.